Charge density distributions and electron scattering form factors of 19F, 22Ne and 26Mg nuclei - Mahmood, Lubna Abduljabbar; Flaiyh , Gaith Naima (Iraqi Journal of Science, 2022)
An effective two-body density operator for point nucleon system folded with thetenser force correlations ( TC's), is produced and used to derive an explicit form forground state two-body charge density distributions (2BCDD's) applicable for19F,22Ne and 26Mg nuclei. It is found that the inclusion of the two-body TC's has thefeature of increasing the central part of the 2BCDD's significantly and reducing thetail part of them slightly, i.e. it tends to increase the probability of transferring theprotons from the surface of the nucleus towards its centeral region and consequentlymakes the nucleus to be more rigid than the case when there is no TC's and alsoleads to decrease the1/ 22 r of the nucleus. It is also found that the effect of theTC's and the effect of increasing the values of  on the 2BCDD's, elastic electronscattering form factors and1/ 22 r are in the same direction for all considerednuclei.